Comparative Understanding of Traditional Architecture based on Literature Review: Refining the Definition of Traditional Architecture (International Journal of Architecture and Urbanism, 2021)
Traditional architecture is often a topic of discussion in the literature as well as in academic discussions and the architect's profession. However, sometimes we also encounter differences in understanding due to different points of view and the literature used. Therefore, this paper aims to re-find the definition of traditional architecture by comparing literature review. The research method used is qualitative descriptive analysis method with  comparative approach to journal literature reviews. There are 10 national journals and 9 international journals that passed through the selection process and become research samples. The results show that the majority of journals explain that traditional architecture is closely related to the culture of the people in a place that identical to the region or ethnicity. Residential houses as a form of architecture are one of the cultural products of hereditary heritage which are motivated by cultural aspects such as religion, customs, beliefs, philosophies, building process rules, and social aspects to show the social stratification of society through symbols and ornaments. Architectural physical aspects studied in traditional architecture include spatial patterns, structures, materials, main access, space boundaries (walls, roofs, floors), window door openings, orientation, and ornament symbols. In addition, there are also some differences in perception between the contents of the journal in several ways that can be discussed further.